2011
DOI: 10.4314/eamj.v87i5.63076
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and experience in needle stick injuries among dental students at the University of Nairobi, Dental Hospital

Abstract: Background: Needle stick injuries (NSI) are the commonest route by which blood borne viruses and/or infections such as HIV, Hepatitis B and C are transmitted from patients to health care workers (HCW). Dental students are also at risk of such infections and injuries due to accidental contamination during their practical occupational exposure. There is hardly any information regarding the knowledge and experiences of NSI among dental students in Kenya. Objective: To determine the knowledge and experiences of NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
2
10
1
Order By: Relevance
“…However, the more advanced semesters, as might be presumed, showed better risk perception than those less advanced, as students in the latter stages are just beginning to form their perceptions of risk. The same result has been described in other studies 2,[9][10][11][14][15][21][22] . In contrast, research performed by Jafari et al 23 demonstrated that students in the final years of an Iranian university's dentistry course showed good risk perception regarding the prevention and transmission of HIV due to their constant contact with sick patients, since these students helped out in a care center for patients with diseases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the more advanced semesters, as might be presumed, showed better risk perception than those less advanced, as students in the latter stages are just beginning to form their perceptions of risk. The same result has been described in other studies 2,[9][10][11][14][15][21][22] . In contrast, research performed by Jafari et al 23 demonstrated that students in the final years of an Iranian university's dentistry course showed good risk perception regarding the prevention and transmission of HIV due to their constant contact with sick patients, since these students helped out in a care center for patients with diseases.…”
Section: Discussionsupporting
confidence: 90%
“…This was also shown in the research conducted by Lima et al 2 , the only difference being the percentage of occupational accidents affecting dental students (59.5%). Likewise, other studies showed higher percentages 9,15,21 , however yet others showed results inferior to those of the present study 8,13 , with sharps injuries being the biggest culprits in occupational accidents in dentistry. As for post-accident measures, it may be inferred from this study that students have not been properly instructed or do not seek to apply the knowledge they have acquired, as only 12% filled in the biological accident notification forms and only 16% asked for the source-patient's serology.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In contrast, Jaber 3 reported NSIs in only 23% of dental students in their study of 230 students, and among these injuries, 26% injuries occurred while recapping of the needles. Furthermore, a study by Mungure et al 10 found NSIs in 29% of the dental students. In the present study, almost all the participants had habit of recapping the needles after use, and around 60% of subjects were vaccinated against hepatitis B.…”
Section: Discussionmentioning
confidence: 96%
“…Makhoka [13], estimated a non-reporting rate of about 40% in the hospital involved in this study. Studies elsewhere in the world show that 35% to 62% of SSNIs are not reported [14,15,16,17]. This is important to HCWs in this study because they are at greater risk because of the high prevalence of BBPs in the general population in sub-Saharan African countries.…”
Section: Epidemiology Of Ssni and Hcw Riskmentioning
confidence: 91%